Interactions and Acts of Teachers in the Classroom Primary School: Indication Bias - Rulyansah, Afib (Universitas Pendidikan Ganesha, 2022)
Recent studies have incorporated teacher implicit assessment bias, with some suggesting that such bias could be used to predict student performance in class. The aim of this study was to analyze teachers' daily interactions with their students to identify potential biases in their practice. This study uses a qualitative exploratory field research format. This study involved twenty elementary school teachers as subjects. The data collection method in this study is observation. Each teacher was observed for 4 hours in an exploratory qualitative study. This study applies thematic analysis techniques to find patterns across the data. The validity and reliability of the research includes external validity, internal validity, and reliability. The results of this research suggest that one possible explanation for the prejudice we see is that it is mediated by the different ways in which teachers behave. However, some educators show bias. Bias can be shown in a variety of nonverbal and academic exchanges. Student achievement within the school system can be affected by teachers treating students differently.